MatrixConverter: Facilitating construction of phenomic character matrices1. (9th February 2015) - Liu, Jing; Endara, Lorena; Burleigh, J. Gordon
Abstract : Premise of the study: While numerous software packages enable scientists to evaluate molecular data and transform them for phylogenetic analyses, few such tools exist for phenomic data. We introduce MatrixConverter, a program that helps expedite and facilitate the transformation of raw phenomic character data into discrete character matrices that can be used in most evolutionary inference programs. Methods and Results: MatrixConverter is an open source program written in Java; a platform‐independent binary executable, as well as sample data sets and a user's manual, are available athttps://github.com/gburleigh/MatrixConverter/tree/master/distribution . MatrixConverter has a simple, intuitive user interface that enables the user to immediately begin scoring phenomic characters. We demonstrate the performance of MatrixConverter on a phenomic data set from cycads. Conclusions: New technologies and software make it possible to obtain phenomic data from species across the tree of life, and MatrixConverter helps to transform these new data for evolutionary or ecological inference.